2007
DOI: 10.1016/j.jacc.2007.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors, But Not C-Reactive Protein, Predict Progression of Calcific Aortic-Valve Disease

Abstract: In this large population-based cohort, approximately 9% of subjects with aortic sclerosis progressed to aortic stenosis over a 5-year follow-up period. There was no association between CRP levels and the presence of calcific aortic-valve disease or incident aortic stenosis. C-reactive protein appears to be a poor predictor of subclinical calcific aortic-valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 38 publications
4
107
4
3
Order By: Relevance
“…4,6,20 However, prognostic factors are likely to differ between the early and late stages, and moreover, the Cardiovascular Health Study has shown the effects of ethnicity on CAVD pathogenesis. 6 This retrospective study analyzed data from Japanese patients and showed that early-stage subjects with mitral regurgitation, nonuse of ARBs or warfarin use tended to undergo progression of CAVD. In late-stage subjects, progression was associated with female gender, small LV cavity and low level of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,6,20 However, prognostic factors are likely to differ between the early and late stages, and moreover, the Cardiovascular Health Study has shown the effects of ethnicity on CAVD pathogenesis. 6 This retrospective study analyzed data from Japanese patients and showed that early-stage subjects with mitral regurgitation, nonuse of ARBs or warfarin use tended to undergo progression of CAVD. In late-stage subjects, progression was associated with female gender, small LV cavity and low level of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…The group with early-stage CAVD comprised subjects with calcification on one or no leaflet and peak aortic transvalvular flow velocity o2 m s À1 (n¼157). 6,[17][18][19] The late-stage CAVD group comprised subjects with two or three calcified aortic valves and/or with peak aortic transvalvular flow velocity of X2 m s À1 (n¼399). Eleven patients had bicuspid aortic valve, and all met the criteria for late-stage CAVD.…”
Section: Methods Subjectsmentioning
confidence: 99%
See 3 more Smart Citations